(untitled) (Bangladesh Journal of Botany, 2021)
Chickpea (Cicer arietinum L.) is severely affected by Fusarium oxysporum sp. ciceris causing vascular wilt disease accounting about 10% of yield losses. The present study was conducted to assess the potential of compatible dual inoculants of Mesorhizobium sp. and PGPR (rhizospheric and endophytic) in initiating and boosting the antioxidant response towards the phytopathogen in vivo under wilt sick conditions in chickpea. Among the different dual inoculated treatments, LGR191+NE8 (Mesorhizobium sp. + nodule endophyte) showed maximum augmentation in the antioxidants viz., catalase (15.16 U/min/g fresh weight of root), guaiacol peroxidase (2.492mmoles/min/g fresh weight of root) and total phenolics (110.25 tannic acid equivalents/g fresh weight of root) over recommended fungicide (captan). Percent wilt control was highest with LGR191+NE8 (95.77%) followed by LGR1+LPGPR-1 (94.17%) after 120 days of sowing. The results suggested an expanded antioxidant state of the wilt infected plants with the dual inoculation of Mesorhizobium sp. with PGPR (rhizospheric and endophytic) decreasing fungal proliferation sustainably. Bangladesh J. Bot. 50(2): 359-364, 2021 (June)